THE ECONOMIC NATURE OF MODERN MONEY - A. V. Berdyshev (Вестник университета)
The evolution of forms and types of money has been сonsidered. The features of the economic nature and the issue of modern credit money have been determined. Based on the study of the mechanism of providing liquidity in order to refinance commercial banks in various countries, the features of forming the monetary base and, accordingly, the emission mechanism in the modern economy have been identified. The specificity of the formation of the monetary base of the Bank of Russia at various stages of development of the Russian economy has been defined. Special attention has been paid to the study of the economic nature of emerging in the conditions of development of digital technologies of electronic money and virtual currencies.